Guanxi and school success: an ethnographic inquiry of parental involvement in rural China. Issue 7 (2nd October 2016) - Xie, Ailei; Postiglione, Gerard A.
Abstract : This study examines the differential patterns of school success of rural students as a result of China's market transition. The process dimension, how families from different social backgrounds within rural society get involved in rural schooling and how this contributes to the inequality of school success within rural society, is investigated. The data analysis suggests that schools as institutions provide few official channels for rural parents to participate in rural schools and help their children to achieve school success. This raises the importance of families' strategic initiatives to employ guanxi within family, community and between school and family. These make the point that guanxi and their employment have become an important mechanism for social inclusion and exclusion in the competition for advantages in school success in post-socialist China.